Exploring Ethnomathematics in the Activities of Traders at the Niki-Niki Traditional Market - Misa, Yeni; Son, Aloisius Loka; Laja, Yosepha Patricia Wua (Brillo Journal, 2024)
Mathematics is a form of culture inherent in all aspects of society's life. In the cultural practices of certain communities, mathematical concepts are involved. There is an intersection between culture and mathematics. Therefore, this research is conducted to explore the mathematical concepts used by traders. This study was conducted at the Niki-Niki Traditional Market. The research subjects consist of 6 individuals, with 2 betel nut sellers, 2 chili pepper sellers, and 2 woven fabric sellers. The data in this study are primary data collected through observation, interviews, and documentation techniques. Data analysis employs the techniques of ethnographic research data analysis, including domain analysis, taxonomic analysis, componential analysis, and cultural theme analysis. The results of the research indicate that there are mathematical concepts of plane geometry and integers in the activities of traders. Concepts of plane geometry include points, rectangles, circles, rhombuses, straight lines, curved lines, and fractal geometry. Meanwhile, mathematical concepts related to integers include sets, counting, addition, subtraction, division, and multiplication.